Towards the Prevention of Aminoglycoside-Related Hearing Loss - O’Sullivan, Mary E.; Perez, Adela; Lin, Randy; Sajjadi, Autefeh; Ricci, Anthony J.; Cheng, Alan G. (Frontiers in Cellular Neuroscience, 2017)
Aminoglycosides are potent antibiotics deployed worldwide despite their known side-effect of sensorineural hearing loss. The main etiology of this sensory deficit is death of inner ear sensory hair cells selectively triggered by aminoglycosides. For decades, research has sought to unravel the molecular events mediating sensory cell demise, emphasizing the roles of reactive oxygen species and their potentials as therapeutic targets. Studies in recent years have revealed candidate transport pathways including the mechanotransducer channel for drug entry into sensory cells. Once inside sensory cells, intracellular targets of aminoglycosides, such as the mitochondrial ribosomes, are beginning to be elucidated. Based on these results, less ototoxic aminoglycoside analogs are being generated and may serve as alternate antimicrobial agents. In this article, we review the latest findings on mechanisms of aminoglycoside entry into hair cells, their intracellular actions and potential therapeutic targets for preventing aminoglycoside ototoxicity.